2018
DOI: 10.1088/1674-4527/18/1/11
|View full text |Cite
|
Sign up to set email alerts
|

High amplitudeδScuti star BO Lyn with evidence of a late A-type companion in an elliptical orbit

Abstract: We present 145 times of light maximum for high amplitude δ Scuti star BO Lyn based on several sky surveys (CRTS, DASCH, NSVS, OMC and SuperWASP) and our photometric observations. Combining with the data in literature, a total of 179 times of light maximum are used to analyze the O − C diagram of BO Lyn. We find that it can be described by an upward parabolic component and a periodic variation with a period of 34.5 ± 0.1 yr. The latter could be caused by the light travel time effect as a result of an additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The periodic change can be well fitted by a sinusoidal curve with a period of 11.82 yr and an amplitude of 0.0106 days. The sinusoidal variation may be caused by the orbit motion in a binary system (Lampens et al 2018;Murphy et al 2018), i.e., the light-travel time effect in δ Scuti-type pulsating star, such as BL Cam (Fauvaud et al 2006), AN Lyncis (Li et al 2010), and BO Lyn (Li et al 2018). If it is true, combining the previous absolute parameters of the target and the mass function, the parameters of the companion can be calculated by the following formulae,…”
Section: Discussionmentioning
confidence: 99%
“…The periodic change can be well fitted by a sinusoidal curve with a period of 11.82 yr and an amplitude of 0.0106 days. The sinusoidal variation may be caused by the orbit motion in a binary system (Lampens et al 2018;Murphy et al 2018), i.e., the light-travel time effect in δ Scuti-type pulsating star, such as BL Cam (Fauvaud et al 2006), AN Lyncis (Li et al 2010), and BO Lyn (Li et al 2018). If it is true, combining the previous absolute parameters of the target and the mass function, the parameters of the companion can be calculated by the following formulae,…”
Section: Discussionmentioning
confidence: 99%
“…We suspected it to be a binary, and therefore vertically displaced in absolute magnitude, as the dominant mode of HADS should fall on the fundamental-mode P-L sequence. Indeed, Li et al (2018) suggested it has an A-type companion in a 35-yr orbit, based on variations in the pulsation phase over the past century.…”
Section: Second Ridge Starsmentioning
confidence: 99%